Comparison of Serum Uric Acid, Iron and Total Iron Binding Capacity (TIBC) Levels in Pre-eclamptic and Normal Pregnant Women - Bita Eslami; Ashraf Moeini; Reihaneh Hosseini; Mojtaba Sedaghat (Tehran University of Medical Sciences, 2010)
Objective: The objective of our study was to compare uric acid, iron and TIBC levels in normal and preeclamptic pregnant women and determine their relations with maternal and fetal complications. Materials and methods: A case control study was conducted in 200 normal and preeclamptic pregnant women. At 32-40 weeks of pregnancy (third trimester) a blood test was taken in order to measure the uric acid, iron and TIBC and their relation with maternal and fetal complications. Results: Uric acid level showed significant difference (4.58 ± 0.73, 4.87 ± 0.58, p=0.002) between  two groups of pre-eclamptic and normal women.  The iron and TIBC level had no significant difference in either group. The uric acid level and iron had significant differences between two groups with and without maternal complication, respectively (4.69 ± 0.66, 5.05 ± 0.59, p<0.05) (387.42 ± 82,  405.24 ± 57, p<0.05). There was not any difference in three parameters between groups with and without fetal complication. The BMI was significantly higher in preeclamptic group and has positive relation with uric acid level. If we consider 29 as BMI cut-off point; it will be associated with 73% sensitivity and 67% specificity in preeclampsia determination. Using 4.55 as uric acid cut-off point, the sensitivity is 76% and specificity is 49%. Conclusion: Although the higher level of uric acid, higher BMI scale and positive roll-over test are associated with preeclampsia, but they are not very strong predictors as single test.